Analisis Kinerja Petugas Rekam Medis di Rumah Sakit Umum Daerah Besemah Kota Pagar Alam - Ratna Dewi; Lilis Suryani; Dian Eka Anggreny (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2021)
The medical record is a permanent legal document that must contain sufficient information to identify the patient, justify the diagnosis and treatment, and record the results. Research Objectives to test the performance of medical records officers with compliance with procedures, storage room standards, the number of medical record personnel, and medical record management training simultaneously with the performance of medical record officers at Besemah Hospital Pagar Alam City. This study is a quantitative study with a cross-sectional research design to determine the independent and dependent variables. Data analysis was carried out univariate, bivariate, and multivariate. The sample in this study were all 62 medical record officers at Besemah Pagar Alam Hospital, and the sample was taken by purposive sampling. Data were collected using a questionnaire and processed using the Chi-Square statistical test. The results showed that medical record officers with high performance were 62.9%, compliance with reasonable procedures was 53.2%, and standard medical record file storage space was adequate, namely 33.9%, the number of medical record personnel was sufficient, namely 54.8%, training good medical record that is 62.9%. The most dominant variable is adherence to standard operating procedures, whose value is less than 0.05 with an OR value of 5.100. Based on the results of the study, it is recommended that the Besemah Hospital, Pagar Alam City, especially the hospital management, need to focus on the aspect of compliance with the fixed procedures that have been set by the hospital and conduct medical record management training to improve the performance of medical record officers.